The systems administrative and their incidence in the management of the risk of disasters, Huanuco, 2022 - Almirco-Benancio, Jhony (2023)
Objective. Determine the incidence of the systems administrative in the management of the  risk of disasters on the servers of the Direction Regional of Health (DIRESA), Huanuco, 2022. Methods. A quantitative, explanatory, applied study with a non-experimental, transectional, correlational-casual design was carried out. The population was compoud by 381 administrative servers of the DIRESA Huanuco, between named and the administrative servers contract (CAS), and it's obtained a sample probabilistic of 188 servers. The valoration was at a level of confidence of the 95 % and a 5 % margin of error. The were used techniques for the test of correlation Spearman's rho. The level of significance established was reason of r=0.839 with a value of p=0,000 less than 0,05. Results. The findings demonstrated that the dimensions of the “administrative systems” are related to the variable “disasters risk management” in: i) planning strategic, with a correlation very strong (r=0,835 and sig. 0,000), ii) management of resources human, with a correlation very strong (r=0,769 and sig. 0,000), iii) supplying, with a correlation very strong (r=0,855 and sig. 0,000), y iv) budget public, with a considerable correlation (r=0,644 and sig. 0,000). Conclusions. The “administrative systems” have a significant incidence on “disasters risk management” in the DIRESA Huanuco servers, evidencing a very strong degree of correlation between the variables at a reason of r=0,839 with a significance value of p=0,000 less than 0,05; is say, to mitigate the risks of imminent disasters in the Huanuco region (Peru), is essential the timely management of administrative systems.